UNINTENTIONAL FINALISM . AN ARISTOTELIAN A PPROPRIATION OF PLATONIC VOCABULARY OF PARTICIPATION - Díaz, Maria Elena (AADEC - UNL, 2018)
Beyond Aristotle's criticisms of the Platonic notion of participation, there are some uses of this term that deserve to be addressed in the Aristotelian work, since they suppose both a Platonic inheritance and a resignification in a diverse conceptual plexus. This paper explores the Aristotelian use of the notion of participation as a non-intentional finality, in the argument that supports that one of the ways of achieving immortality is procreation, to show how the adoption of the Platonic terminology of participation can be compatible with the Aristotelian causal framework.